Counseling on Oil Bodies Utilization and Mangrove Seed Conservation in Pramuka Island, North Thousand Islands District, Thousand Islands Regency - Buntora Pasaribu; Kalysta Fellatami; Lantun P. Dewanti; Ibnu Faizal (Unpad Press, 2023)
Oil bodies play an important role in storing energy in plants and animals. The structure of oil bodies consists of triacylglycerol surrounded by a layer of phospholipids and bound by unique proteins. Oil bodies are widely found in various organisms such as algae, soil plant, water seeds plants, flowers, pollen, and animals. Mangrove seeds, also known as